منهج الداعية عند الفتن -دراسة تحليلية في كتاب:المنهج الشرعي للداعية عندالفتن للشيخ عبد الله بن حمود الفريح - قويدري, فتيحة; زين, سعاد; مسعي محمد, راضية (University of Eloued-جامعة الوادي, 2022)
"الملخص باللغة العربية : تناولت المذكرة دراسة حول شخصية عالمية معاصرة ، وهو فضيلة الشيخ عبد الله بن حمود الفريح ، وقد حاولنا أن نسلط الضوء على منهج الدعوة إلى الله عند الفتن من وجهة نظر الشيخ المذكور من خلال دراسة كتابه : المنهج الشرعي للداعية عند الفتن . وقد قسمنا البحث إلى جزأين : نطري تطرقنا فيه للتعريف بمصطلحات الدراسة والتعريف بالشخصية المبحوث في فكره ، الشيخ عبد الله بن حمود الفريح ، وتطبيقي : تناولنا فيه مناهج الدعوة الاسلامية من خلال الضوابط الشرعية لمنهج الداعية عند الفتن وهي : الاعتصام بالكتاب و السنة و التبيين و التثبيت في معرفة وثبوت أخبار الفتن ، أصل الانتماء و العبادة في الفتن و افضليتها ، الحق في وقت الفتن و الأصل في تنزيل أحاديثها ، كل فتن في الأمة موصوفة في الشرع ولله تعالى ألطاف ورحمة، وهذه المطالب الأربعة ضرورية في تبليغ الدعوة إلى الله في هذا العصر وغيره وخصوصا مع غير المسلمين لكي تكون أبلغ في الوصول إلى الهدف المنشود وهو توصيل رسالة الاسلام إلى أكبر قدر ممكن من الأنام ""Abstract The memoire dealt with a study on a contemporary global personality, His Eminence Sheikh Abdullah bin Hammoud Al-Fraih, and we have tried to shed light on the approach to the call to Allah during temptation ( Fitan ) from the point of view of the mentioned Sheikh by studying his book: The Religious Approach for the Preacher during Temptations ( Fitan ). We divided the research into two parts: Theoretical in which we tackled an introduction to the terms of the study and to the mentioned personality , Sheikh Abdullah bin Hammoud Al-Fraih . In the practical part , we dealt with the approaches of Islamic da’wah through the religious guidelines of the preacher’s approach to sedition, which are: adherence to the Book ( Qura'an) and the Sunnah, clarification and confirmation in Knowing and proving the news of Fitnah , the origin of belonging and worship in temptations and its priority, the right in the time of temptation ( Fitan ) and the principle in revealing its hadiths. Muslims in order to be more informed in reaching the desired goal, which is to deliver the message of Islam to as many people as possible."
مذكرة ماستر
Keywords: منهج الداعية - الفتن - دراسة تحليلية - المنهج الشرعي للداعية عند الفتن - للشيخ عبد الله بن حمود الفريح; The method of the preacher - sedition - an analytical study - the legal approach of the preacher in the face of sedition - by Sheikh Abdullah bin Hamoud Al-Fraih